The Orravatnsrustir palsa site in Central Iceland - Palsas in an aeolian sedimentation environment - Sæmundsson, Þorsteinn; Ólafur, Arnalds; Christof, Kneisel; Jónsson, Helgi Páll; Decaulne, Armelle (CCSD, 2012)
International audience